PERFORMANCE ANALYSIS OF A MULTIPLE COMPONENT MANUFACTURING SUBSYSTEM OF A RUBBER TUBE PRODUCTION PLANT UNDER PREEMPTIVE RESUME PRIORITY REPAIR - Goyal, Atul; Sharma, S.K; Gupta, Pardeep (International Journal of Industrial Engineering: Theory, Applications and Practice, 2009)
A mathematical model of the gradually deteriorating Rubber Preparation System, a part of a cycle rubber tube manufacturing plant is presented in this paper for improving its availability. The methodology for determining the availability of the system under preemptive resume priority repair discipline is based on Markov Modeling. The system undergoes for preventive maintenance (PM) and corrective maintenance (CM) on its transition to pending-to-failed and failed states respectively. The effect of repair error in preventive maintenance on most vulnerable items of the system is examined to realize the highest level of performance. The failure and repair rates of the different subcomponents of the system are taken as constant. Probability considerations at various stages of the system give differential equations which are solved using Laplace Transform to obtain the state probabilities. Performance analysis of the system has been carried out which helped in identifying the critical factors and assessing their impact on the system availability.